Bamboo Fibres Processing, Properties and Applications - Babu, K. Murugesh; Babu, K. Murugesh; Chandrasekhara, S.M. (Woodhead Publishing, 2022)
Bamboo Fibres: Processing, Properties, and Applications brings together best practices from key stages of bamboo production and application, allowing readers to find new solutions for bamboo fibers. Chapters on bamboo fiber characterization and properties show the full range of functional uses of the material. When used as a replacement for petrochemical-based synthetic fibers, this abundant and cheap material/textile can significantly reduce the environmental impact of textile products. This book is an invaluable resource for fiber chemists, material scientists, fabric technologists, manufacturers, and researchers interested in sustainable textiles. Bamboo fiber is a cellulosic fibre regenerated from the bamboo plant. It is highly sustainable being fully biodegradable and has strength comparable to conventional glass fibers. It has many other valuable characteristics, being bacteriostatic, antifungal, antibacterial, hypoallergenic, hydroscopic, a natural deodorizer, and resistant to ultraviolet light. Furthermore, it is highly durable, stable and tough and has substantial tensile strength. Due to its versatile properties, bamboo fibers are already used in the textile industry to make garments, in biomedical applications due to its antibacterial qualities, and many other areas. - Explores special technical properties of bamboo fibers, including antimicrobial, bacteriostatic, antifungal, antibacterial, hypoallergenic, hydroscopic and mechanical properties - Provides innovative knowledge on the production of bamboo fibers, including the blending of yarns and fabrics - Explains the broader techno-economics of bamboo fiber production, covering the social as well as environmental sustainability of the material